2017
DOI: 10.1371/journal.pone.0179261
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of noble, signal and narrow-clawed crayfish using environmental DNA from freshwater samples

Abstract: For several hundred years freshwater crayfish (Crustacea—Decapoda—Astacidea) have played an important ecological, cultural and culinary role in Scandinavia. However, many native populations of noble crayfish Astacus astacus have faced major declines during the last century, largely resulting from human assisted expansion of non-indigenous signal crayfish Pacifastacus leniusculus that carry and transmit the crayfish plague pathogen. In Denmark, also the non-indigenous narrow-clawed crayfish Astacus leptodactylu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 60 publications
3
113
0
Order By: Relevance
“…We believe that such tools are valuable to identify suitable areas where fieldwork can be conducted for the purpose of local scale site selection. The threat of crayfish plague might also be assessed in sites selected for reintroductions, using environmental DNA to detect A. astaci (Vralstad et al, 2009) or exotic crayfish presence (Agersnap et al, 2017). However, one should be conscious of the limits inherent in such correlative models and account for uncertainties regarding bias in observations or variables used in modelling when designing conservation actions.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that such tools are valuable to identify suitable areas where fieldwork can be conducted for the purpose of local scale site selection. The threat of crayfish plague might also be assessed in sites selected for reintroductions, using environmental DNA to detect A. astaci (Vralstad et al, 2009) or exotic crayfish presence (Agersnap et al, 2017). However, one should be conscious of the limits inherent in such correlative models and account for uncertainties regarding bias in observations or variables used in modelling when designing conservation actions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, eDNA has performed well for representing occupancy of species (Dougherty et al., ; Pilliod et al., ; Smart et al., ), and some studies have found strong agreement between abundance or biomass of organisms and abundance of eDNA in the environment (Doi et al., ; Klobucar et al., ). Specific to crayfishes, studies have generally found eDNA to accurately represent occupancy of crayfishes, potentially with more sensitivity than some conventional methods, but eDNA has performed poorly in reflecting crayfish abundance (Agersnap et al., ; Cai et al., ; Dougherty et al., ; Larson et al., ). In some of these cases, the poor ability of eDNA to estimate abundance relative to conventional sampling methods could be related to weaknesses of the conventional methods themselves; for example, baited trapping of crayfishes has known biases and limitations that could fail to accurately reflect crayfish biomass (Larson & Olden, ; Stuecheli, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a handful of crayfish eDNA studies have shown promising results but have largely focused on lentic environments (e.g. Agersnap et al., ; Cai et al., ; Dougherty et al., ; Mauvisseau et al., ; Tréguier et al., ), although one study (Ikeda, Doi, Tanaka, Kawai, & Negishi, ) used eDNA to successfully detect the endemic Japanese crayfish ( Cambaroides japonicus ) in small headwater streams. Despite these encouraging results, it remains to be seen whether eDNA can reflect presence and abundance of narrowly endemic crayfishes in larger, perennial streams where eDNA transport is more likely to be a problem (Deiner & Altermatt, ).…”
Section: Introductionmentioning
confidence: 99%
“…The LOQ for the set of primers and probe used in this study is higher than that reported in other eDNA studies on crayfish (Table ), this may be due to the longer amplicon used here. However, there is clear need to standardize LOQ and LOD definitions and calculation methods for eDNA studies (Agersnap et al., ). We show that eDNA related to the eggs, rather than the animal itself, may increase the probability of successfully detecting the presence of crayfish, this is especially useful given the need for early detection in combatting invasive species.…”
Section: Discussionmentioning
confidence: 99%